2018
DOI: 10.1111/1748-8583.12180
|View full text |Cite
|
Sign up to set email alerts
|

The role of pay secrecy policies and employee secrecy preferences in shaping job attitudes

Abstract: Although pay secrecy continues to garner attention in human resource management, little research examines how these policies impact employees. Research inconsistently links secretive pay policies to unfavourable outcomes but has yet to consider that employees may have varying attitudes toward these policies. We examine how employee preferences modify the effect that organisational pay secrecy policies have on employee attitudes in a sample of 431 employed adults. To accomplish this goal, we create measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…Pay secrecy policies . We measured distributive pay nondisclosure (e.g., “My employer publishes pay information”), and pay communication restriction (e.g., “My company has rules against discussing employee pay with others”) with the 4‐item scales developed by Smit and Montag‐Smit (2018). A new 4‐item scale measuring procedural pay nondisclosure (e.g., “My employer has clear guidelines for how pay is allocated”) was developed for this study (see Appendix C in Data S1).…”
Section: Study 3 Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pay secrecy policies . We measured distributive pay nondisclosure (e.g., “My employer publishes pay information”), and pay communication restriction (e.g., “My company has rules against discussing employee pay with others”) with the 4‐item scales developed by Smit and Montag‐Smit (2018). A new 4‐item scale measuring procedural pay nondisclosure (e.g., “My employer has clear guidelines for how pay is allocated”) was developed for this study (see Appendix C in Data S1).…”
Section: Study 3 Methodsmentioning
confidence: 99%
“…This study is among the first to examine multiple dimensions of pay secrecy simultaneously (cf. Smit & Montag-Smit, 2018). Additionally, previous pay secrecy research has occasionally observed inconsistent relationships between policy and outcomes (e.g., procedural justice), and a more nuanced conceptualisation and measurement of policy, along with individual differences measures, may help resolve these inconsistencies.…”
Section: Theoretical Implications and Directions For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend has naturally made some employers and human resource (HR) practitioners nervous that greater transparency could expose pay inequalities, cause reputational damage or increase costs (Zenger, 2016). These potential impacts remain understudied in the academic literature, as do the potential impacts of pay transparency on various organisational outcomes such as job turnover and employee satisfaction (Smit & Montag-Smit, 2018;Trotter, Zacur, & Stickney, 2017), making it harder for employers and HR to know how to handle pay transparency.…”
Section: Introductionmentioning
confidence: 99%
“…Even studies that have engaged with people in their role as employees tend to focus on the employer's pay transparency policy (e.g. Marasi et al, 2018;Smit & Montag-Smit, 2018). Smit and Montag-Smit's (2019) later work exploring employee preferences with regard to pay transparency and Scott et al's (2015;Scott, Antoni, Grodzicki, Morales, & Peláez, 2020) studies of global pay transparency preferences are the only research studies, to date, that take an employee-centred stance, and even then, employees' views are assessed through quantitative surveying.…”
Section: Introductionmentioning
confidence: 99%